Effects of murottal al-qur'an therapy on anxiety and vital signs among primigravida pregnant women in pre-operation caesarean section - Yumni, Fathiya Lutfil; Priyantini, Diah; Prabawati, Chlara Yunita; Ayatulloh, Daviq (Universitas Airlangga, 2025)
Introduction: This research aims to analyze the effect of Murottal Al-Qur'an Therapy on reducing anxiety and vital signs in primigravid pregnant women before C-Section surgery. Methods: A quasi-experimental study on pregnant women who will undergo C-Section surgery at a hospital in Surabaya, Indonesia. A total of 84 respondents (42 in the intervention group and 42 in the control group) were recruited using purposive sampling. Anxiety variables were measured using the Zung Self-Rating Anxiety Scale (ZSRAS), and vital signs (pulse, blood pressure, respiration rate) were measured using a sphygmomanometer and a calibrated clock. Data analysis was used to test the Wilcoxon Signed Rank Test and the Mann-Whitney Test. Results: The intervention group's vital signs for blood pressure decreased to 120.98 mmHg and diastolic blood pressure to 70.08 mmHg. The mother's pulse showed an average of 79.95 times per minute and respiration an average of 20 times per minute. Testing the effect of Murottal Al-Qur'an Therapy showed a significant effect on the Intervention group for anxiety (p=0.001), systolic pressure (p=0.005), diastolic pressure (p=0.001), pulse (p=0.005), and respiration rate (p=0.001), respectively. The difference test shows a significant difference after the intervention, with a p-value of <0.001. Conclusions: Murottal Al-Qur'an Therapy can reduce anxiety levels, systolic and diastolic blood pressure, pulse rate, and respiration rate in primigravida pregnant women who will undergo C-Section surgery. So, the results of this research can be applied by primary nurses in maternity rooms or operating rooms for primigravida pregnant patients who will undergo cesarean Section surgery.